Nominalizations as complex strategies of politeness and face-work in scientific papers written in Brazilian Portuguese - Oliveira, Ana Larissa Adorno Marciotto (2017)
In this paper, we depart from the hypothesis that face-work is an important dimension of the construction of discourse, regardless the register (oral or written). Drawing on the framework of Pragmatics, we argue that instances of nominalization can operate as politeness strategies, in the sense that they permit, on the one hand, the omission of the actor/agent of a given verbal event and, on the other hand, they contribute to establishing the boundaries of social distance and power relations, as a pervasive feature of formal texts. The empirical data analyzed in this study include academic papers taken from the Academic Corpus of Brazilian Portuguese (CAPB). In the academic papers analyzed, nominalizations operated, to a large degree, as a strategy to mitigate the potential attacks on the positive face of the author himself, acting, therefore, as a strategy of positive politeness.